Potential contributions of nitrifiers and denitrifiers to nitrous oxide sources and sinks in China's estuarine and coastal areas - X. Dai; M. Chen; X. Wan; E. Tan; J. Zeng; N. Chen; N. Chen; S.-J. Kao; S.-J. Kao; Y. Zhang (Biogeosciences, 2022)
Nitrous oxide (N2O) is an important ozone-depleting greenhouse gas produced and consumed by microbially mediated nitrification and denitrification pathways. Estuaries are intensive N2O emission regions in marine ecosystems. However, the potential contributions of nitrifiers and denitrifiers to N2O sources and sinks in China's estuarine and coastal areas are poorly understood. The abundance and transcription of six key microbial functional genes involved in nitrification and denitrification, as well as the clade II-type nosZ gene-bearing community composition of N2O reducers, were investigated in four estuaries spanning the Chinese coastline. The results showed that the ammonia-oxidizing archaeal amoA genes and transcripts were more dominant in the northern Bohai Sea (BS) and Yangtze River estuaries, which had low nitrogen concentrations, while the denitrifier nirS genes and transcripts were more dominant in the southern Jiulong River (JRE) and Pearl River estuaries, which had high levels of terrestrial nitrogen input. Notably, the nosZ clade II gene was more abundant than the clade I-type throughout the estuaries except for in the JRE and a few sites of the BS, while the opposite transcript distribution pattern was observed in these two estuaries. The gene and transcript distributions were significantly constrained by nitrogen and oxygen concentrations as well as by salinity, temperature, and pH. The nosZ clade II gene-bearing community composition along China's coastline had a high level of diversity and was distinctly different from that in the soil and in marine oxygen-minimum-zone waters. By comparing the gene distribution patterns across the estuaries with the distribution patterns of the N2O concentration and flux, we found that denitrification may principally control the N2O emissions pattern.